Effects of feral free‐roaming horses on semi‐arid rangeland ecosystems: an example from the sagebrush steppe. Issue 10 (22nd October 2014) - Davies, K. W.; Collins, G.; Boyd, C. S.
Abstract : Feral horses ( Equus caballus ) are viewed as a symbol of freedom and power; however, they are also a relatively unmanaged, non‐native grazer in North America, South America, and Australia. Information about their influence on vegetation and soil characteristics in semi‐arid rangelands has been limited by confounding effects of cattle ( Bos taurus ) grazing and a lack of empirical manipulative studies. We compared vegetation and soil surface characteristics in feral horse grazed areas and ungrazed exclosures at five sagebrush ( Artemisia ) steppe sites in northern Nevada. Horse grazed areas had lower sagebrush density and plant diversity, greater soil penetration resistance, and lower soil aggregate stability than ungrazed areas. Herbaceous cover and density generally did not differ between grazed and ungrazed treatments, with the exception of heavily grazed sites in which perennial grass cover was reduced. The cumulative effect of feral horses on soil characteristics suggests that they may affect the ecological function of semi‐arid rangelands by increasing the risk of soil erosion and potentially decreasing availability of water for plant growth. The two‐fold increase in sagebrush density with horse exclusion suggests that feral horses may limit sagebrush recruitment and thereby negatively impact Greater Sage‐grouse ( Centrocercus urophasianus ) and other sagebrush associated wildlife. The effects of feral horses on sagebrush and other semi‐arid ecosystems should be considered when developing conservation plans for these ecosystems and associated wildlife.